Development of a German version of the oral health assessment tool - Klotz, Anna-Luisa; Zajac, Melania; Ehret, Judith; Hassel, Alexander J.; Rammelsberg, Peter; Zenthöfer, Andreas (Aging clinical and experimental research, 2020)
Limited assessment tools for estimating the oral health of nursing home residents are available in the German language. To develop a German version of the Oral Health Assessment Tool (OHAT) and to evaluate test–retest and inter-examiner reliability in use for the assessment of nursing home residents’ oral health by caregivers before and after dental training.
Published online: 7 March 2019
Gesehen am 03.03.2020